Prisoner : my 544 days in an Iranian prison–solitary confinement, a sham trial, high-stakes diplomacy, and the extraordinary efforts it took to get me out /: my 544 days in an Iranian prison–solitary confinement, a sham trial, high-stakes diplomacy, and the extraordinary efforts it took to get me out. ([2019]) - Rezaian, Jason
No abstract available